Reconstructing a plasmonic metasurface for a broadband high-efficiency optical vortex in the visible frequency. Issue 26 (14th June 2018) - Lu, Bing-Rui; Deng, Jianan; Li, Qi; Zhang, Sichao; Zhou, Jing; Zhou, Lei; Chen, Yifang
Abstract : We optimized a Berry-phase-based metasurface for high quality vortex generation in optical frequencies with a >20% efficiency enhancement in a broad waveband. Abstract : Metasurfaces consisting of a two-dimensional metallic nano-antenna array are capable of transferring a Gaussian beam into an optical vortex with a helical phase front and a phase singularity by manipulating the polarization/phase status of light. This miniaturizes a laboratory scaled optical system into a wafer scale component, opening up a new area for broad applications in optics. However, the low conversion efficiency to generate a vortex beam from circularly polarized light hinders further development. This paper reports our recent success in improving the efficiency over a broad waveband at the visible frequency compared with the existing work. The choice of material, the geometry and the spatial organization of meta-atoms, and the fabrication fidelity are theoretically investigated by the Jones matrix method. The theoretical conversion efficiency over 40% in the visible wavelength range is worked out by systematic calculation using the finite difference time domain (FDTD) method. The fabricated metasurface based on the parameters by theoretical optimization demonstrates a high quality vortex in optical frequencies with a significantly enhanced efficiency of over 20% in a broad waveband.